Fueling Life on Wheels (FLOW) – a single-subject study on the effects of a dance program on the self-esteem and confidence of pediatric manual wheelchair users. - Legue, Anna; Vanderburgh, Dana; Seigel, Brynn; Chase, Tony (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: The pilot Fueling Life on Wheels program was developed to engage pediatric manual wheelchair users in the joy that is the art of dance. This study tests the hypothesis that a dance program will further increase self-esteem and confidence in pediatric manual wheelchair users. Materials and Methods: Professional dance choreographers and occupational therapy doctoral students worked together to provide a 5-night series of dance class activities for children who are wheelchair users. The Rosenberg Self-Esteem Scale, Coopersmith Self-Esteem Inventory, and Pediatric Wheelchair-User Fear of Falling Scale measured participants' self-esteem as well as confidence and ability to complete wheelchair skills. Semi-structured, caregiver interviews were also conducted. Results: The study resulted in increases in self-esteem for both participants. Participants noted either a decrease or no change in fear of falling out of their chair. The caregiver interviews denoted overall program satisfaction which is a crucial component of the program. Conclusion: Limited sample sizes for this pilot study allowed for a multiple single subject design. Though larger studies are warranted, the program demonstrated a positive influence on the participants and developed pragmatic data for future iterations. IMPLICATIONS FOR REHABILITATION: Dance, a medium traditionally not geared at wheelchair users (or specifically pediatric wheelchair users) can be an effective strategy for meaningful engagement and increased self-esteem. Pediatric programs with dance activities can serve as a method for boosting social participation among children with disabilities. This work opens the door for future work studying the impact of dance for children with disabilities.